La relación entre el bienestar laboral y la gestión del cambio en una entidad financiera en el Departamento del Meta, Colombia; Relationship between labor well-being and change management in a financial entity in the Department of Meta, Colombia - Dagoberto Torres-Flórez; Lebsy Jazmín Hernández Calderón; Lisset Rocío Medina Moreno (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– This study was conducted to analyze the relationship between well-being at work and change management among employees of a financial institution located in the department of Meta, Colombia. The information was collected via a questionnaire sent to all employees in 2021. A statistical and correlational analysis was carried out. The results show that (1) the majority of participants present high levels of well-being at work, (2) the sociodemographic characterization of the collaborators shows a greater presence of women (70%), and (3) the highest percentage of employees belong to the commercial field (53%). It was found that wellness activities have a significant relationship with change management in the organization. The financial entity has implemented actions that generate well-being in employees, however, it is important to improve some aspects related to change management and continue advancing in policies that favor the reconciliation of family and work life.
Keywords: M12; M54; J28; J32; 330; Organizational management; Employee satisfaction; Financial Entity